An Unfortunate Mistake or a Witkacy Dodge? - Degler, Janusz (Przestrzenie Teorii, 2020)
In the Poetry of Philosophers anthology (Kraków–Wrocław 1984) Wit Jaworski published 221 works by 114 authors, starting with Tales from Milet to John Paul II. Almost all known philosophers composed poetry, which often complemented their philosophical reflections or concepts. The list of names also includes Stanisław Ignacy Witkiewicz, who wrote poems from his youth until his death, although at the same time regretting that he had no poetic talent and used some of his works in his dramas as examples of a graphomaniac’s work. Many poems have a humorous and parodical, which brings them closer to his numerous grotesque drawings. They were collected and published by Anna Micińska in an album entitled Wistość tych rzeczy jest nie z świata tego (Kraków 1977), illustrated by Urszula Kenar. In the anthology, under the name of Witkiewicz, there is a poem which begins with words: “Otom jest zwyciężony/ Ginę zgubą wszelkiego żywego stworzenia”. There is no doubt that this is the beginning of the third stanza of the well-known poem by Czesław Miłosz entitled St. Ign. Witkiewicz, published in the volume Ocalenie (Warsaw 1945). Is it an unfortunate mistake on the part of the author of the anthology, a seasoned critic and experienced editor, or is it his fortune to confuse the censor, who did not allow Miłosz’s texts to be published and thus to “smuggle” his poem in under the guise of Witkiewicz? The puzzle remains unresolved. The mistake is inscribed in the history of Witkacy’s so-called “dodges”, which he did to his friends and acquaintances, and then to those who dealt with his life and work. To attribute to him the authorship of Miłosz’s excellent work would certainly make him happy.